Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

One-pot synthesis of 5-hydroxymethylfurfural by cellulose hydrolysis over highly active bimodal micro/mesoporous H-ZSM-5 catalyst - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Thakur, Pratika; Sawant, Sanjay D.; Zambre, Vishal P.; Bokade, Vijay V. (ACS Sustainable Chemistry & Engineering, 2014)
Direct synthesis of 5-hydroxymethylfurfural (5-HMF), a useful renewable biofuel and biochemical, was systematically studied by hydrolysis of microcrystalline cellulose over Bimodal-HZ-5 zeolite. Bimodal-HZ-5 zeolite obtained by post-synthesis modification of H-ZSM-5 with desilication was found to be a potential heterogeneous catalyst with 67% cellulose conversion and 46% yield of 5-HMF. Bimodal-HZ-5 was observed to be reusable for four cycles, without any loss in activity. The detailed optimization of process parameters and catalyst reusability are also presented. The present study opens a new avenue for the renewable one-pot synthesis of 5-HMF, a valuable product.
Keywords: 5-Hydroxymethylfurfural; Biomodal-HZ-5; glucose; Hydrolysis; Microcrystalline cellulose

Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide